Targeting Lymphatics for Nanoparticle Drug Delivery - McCright, Jacob; Naiknavare, Ritika; Yarmovsky, Jenny; Maisel, Katharina (Frontiers in Pharmacology, 2022)
The lymphatics transport material from peripheral tissues to lymph nodes, where immune responses are formed, before being transported into systemic circulation. With key roles in transport and fluid homeostasis, lymphatic dysregulation is linked to diseases, including lymphedema. Fluid within the interstitium passes into initial lymphatic vessels where a valve system prevents fluid backflow. Additionally, lymphatic endothelial cells produce key chemokines, such as CCL21, that direct the migration of dendritic cells and lymphocytes. As a result, lymphatics are an attractive delivery route for transporting immune modulatory treatments to lymph nodes where immunotherapies are potentiated in addition to being an alternative method of reaching systemic circulation. In this review, we discuss the physiology of lymphatic vessels and mechanisms used in the transport of materials from peripheral tissues to lymph nodes. We then summarize nanomaterial-based strategies to take advantage of lymphatic transport functions for delivering therapeutics to lymph nodes or systemic circulation. We also describe opportunities for targeting lymphatic endothelial cells to modulate transport and immune functions.